Notes on the Impact of Lawyer Performance on the administration of Justice in Mexico - (:unkn) unknown (My University, 2016)
This paper has the purpose of highlighting the role of lawyers in the justicesystem. It attempts to provide a basic conceptual framework for the analysis of lawyerperformance as it relates to the operation of the administration of justice in Mexico,especially in criminal cases. For such purpose, and after presenting an overview of legaleducation and the legal profession in Mexico, the professional effectiveness of lawyersand their role as intermediaries between the justice system and society are examined. Thisallows identifying the main avenues for future reform, but much will depend also onhaving a more detailed and precise description of the actual behavior of lawyers and onan open and public debate on their proper role in the judicial process.